Post-Dobbs Realities: Ethical Imperatives for Data Transparency and Trust in Maternal Health Care. - Fletcher, Faith E.; Schott, Sophie L.; Akhiemokhali, Kelley; White, Kari (American Journal of Public Health, 2026)
The authors discuss improving transparency and public trust in maternal health care data following the 2022 U.S. Supreme Court decision on the abortion rights case Dobbs v. Jackson Women's Health Organization. Topics explored include the evaluation of maternal health outcomes by state maternal mortality review committees (MMRC) and the significant contribution of MMRC to the Maternal Mortality Review Information Application System of the U.S. Centers for Disease Control and Prevention (CDC).